Anti-parasitic Activity of Some Medicinal Plants Essential Oils on Giardia lamblia and Entamoeba histolytica, In Vitro - Mohammad Azadbakht; Aroona Chabra*; Ali Saeedi Akbarabadi; Mohammad Hossein Motazedian; Taha Monadi; Fatemeh Akbari (Research Journal of Pharmacognosy, 2020)
Background and objectives: Giardiasis and amoebiasis are two common diseases in human societies which make increasing problems for the health managing systems. In the present study, the antiparasitic activity of Allium sativum, Artemisia sieberi, Zatraria multiflora, Chenopodium botrys and Eucalyptus globulus essential oils on Giardia lamblia cysts and Entamoeba histolytica trophozoites were investigated in vitro. Methods: Giardia lamblia cysts and E. histolytica trophozoites were isolated from infected sample stools. The parasites were treated by four concentrations (0.2, 0.1, 0.01 and 0.001 µg/mL) of essential oils, separately for 30 min at 37 °C. Results: Theessential oils at the concentration of 0.1 and 0.2 µg/mL indicated appreciate parasiticidal effect (p<0.05).  Eucalyptus globulus had maximum efficacy on both G. lamblia and E. histolytica with mortality rates of 79.7% and 87.6% within 30 min. Conclusion: All essential oils showed potent anti-giardiasis and anti-amoebiasis activity. Also, E. globulus with the highest efficiency could be considered as anti-protozoa medication to use an adjunct or primary therapy.